Oxidation of protein disulfide bonds by singlet oxygen gives rise to glutathionylated proteins - Jiang, Shuwen; Carroll, Luke; Rasmussen, Lars M.; Davies, Michael J. (Redox biology, 2021)
Disulfide bonds play a key function in determining the structure of proteins, and are the most strongly conserved compositional feature across proteomes. They are particularly common in extracellular environments, such as the extracellular matrix and plasma, and in proteins that have structural (e.g. matrix) or binding functions (e.g. receptors). Recent data indicate that disulfides vary markedly with regard to their rate of reaction with two-electron oxidants (e.g. HOCl, ONOOH), with some species being rapidly and readily oxidized. These reactions yielding thiosulfinates that can react further with a thiol to give thiolated products (e.g. glutathionylated proteins with glutathione, GSH). Here we show that these ‘oxidant-mediated thiol-disulfide exchange reactions’ also occur during photo-oxidation reactions involving singlet oxygen (1O2). Reaction of protein disulfides with 1O2 (generated by multiple sensitizers in the presence of visible light and O2), yields reactive intermediates, probably zwitterionic peroxyl adducts or thiosulfinates. Subsequent exposure to GSH, at concentrations down to 2 μM, yields thiolated adducts which have been characterized by both immunoblotting and mass spectrometry. The yield of GSH adducts is enhanced in D2O buffers, and requires the presence of the disulfide bond. This glutathionylation can be diminished by non-enzymatic (e.g. tris-(2-carboxyethyl)phosphine) and enzymatic (glutaredoxin) reducing systems. Photo-oxidation of human plasma and subsequent incubation with GSH yields similar glutathionylated products with these formed primarily on serum albumin and immunoglobulin chains, demonstrating potential in vivo relevance. These reactions provide a novel pathway to the formation of glutathionylated proteins, which are widely recognized as key signaling molecules, via photo-oxidation reactions. [Display omitted] •Disulfide bonds (DSBs) are critical to protein structure and function.•DSBs are rapidly oxidized by singlet oxygen and other oxidants to reactive species.•These DSB-derived intermediates react with GSH to give glutathionylated proteins.•Glutathionylation can be diminished by reductants, but does not repair DSB damage.•Oxidation of human plasma DSBs gives glutathionylated albumin and immunoglobulins.